If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 8y + -6 = 6y + 6 Reorder the terms: -6 + 8y = 6y + 6 Reorder the terms: -6 + 8y = 6 + 6y Solving -6 + 8y = 6 + 6y Solving for variable 'y'. Move all terms containing y to the left, all other terms to the right. Add '-6y' to each side of the equation. -6 + 8y + -6y = 6 + 6y + -6y Combine like terms: 8y + -6y = 2y -6 + 2y = 6 + 6y + -6y Combine like terms: 6y + -6y = 0 -6 + 2y = 6 + 0 -6 + 2y = 6 Add '6' to each side of the equation. -6 + 6 + 2y = 6 + 6 Combine like terms: -6 + 6 = 0 0 + 2y = 6 + 6 2y = 6 + 6 Combine like terms: 6 + 6 = 12 2y = 12 Divide each side by '2'. y = 6 Simplifying y = 6
| 6(3+2x)=54 | | x^2-13x+15=-3x-1 | | 7x+2=12+x | | -16x-20=-13x+55 | | (a+b+c)*(a+b-c)= | | 7x^2+28x-315=0 | | 10=42-2x | | 7x+21=4+2x | | 6(7+2x)=114 | | 2x-3+5x-8=6x+54 | | x^2+4x+10=7 | | x^2+2x=1000 | | 5a-6=3a-8 | | 0=6x^2+5sp-6p^2 | | 8(e-1)=5e+2 | | 3x^2-54x+240=0 | | 6x^2+5sp-6p^2=0 | | 14x+1=21x+4 | | .25x+9=13 | | 3y^2-12y-8=0 | | 6x^2+1x-5=0 | | 1=6x+4 | | 5(x+2)=12+x | | 29x-13y=11 | | 4x+5x-y+3x= | | x^2+3x-2=-2 | | ln(2y-5)-lny+3=0 | | 5x-7=2x+4 | | ym=bd | | lny-5ln+3=0 | | (2x+18)(3x+5)(2x+17)=180 | | 12+3x=7x+12 |